THE LATEST METHODS OF TEACHING A FOREIGN LANGUAGE IN CIVIL SERVANTS` TRAINING - Astapova , T. (Theory and Practice of Public Administration, 2020)
The article considers theoretical aspects of studying English by civil servants, including a number of modern methods of teaching in distance with increased motivation of students. It is also given the characteristic of technology and modern approaches techniques from the point of the mixed training when studying foreign languages. A practical study of the effectiveness of the English language teaching with the help of information and communication technologies are discussed. The author writes about some of the most creative approaches that can deliver the results you need: stimulating debate and discussion – encouraging students to discuss a variety of topics: political heroes of popular TV shows, different debates, future scenarios, improvements they would like to see in their community or environment and everything else that motivates them to talk, discuss the research topics. From time to time there is a debate of some sensational innovation in the life of the world or a taboo idea that other teachers will not touch. Discussion outside the established curriculum gives students more freedom of expression, and debate is an element of competition that is entirely language-based. Creating a list of grammar-based programs is another way to improve learning. Teaching students the concept of grammar and composition is not just about theory, but more about practice. The number of hours they spend in class is limited, but they have round-the-clock access to a smartphone, a tablet or a laptop. Using the power of web tools creates a list of the best programs and games that you can use to teach English. Providing students with such a list will help them build their vocabulary, explore interactive learning platforms, and improve their grammar through constant practice and endurance. Maximizing the potential of online tools is the use of smart classroom technologies to monitor students’ progress, encourage them to try online learning tools and interact with English on social networking platforms. These non-traditional teaching methods resonate in any age group of students who completely study at home online. The e-network offers a virtually endless set of reading materials for English learners, from free e-books and stories to social media content, translation tools and blog posts. Although speaking the language is important, reading allows students to understand concepts independently and to form their vocabulary faster. Creating an inspiring learning environment is something that promotes learning. If foreign language teaching takes place in the physical space, added resources encourage students to learn. For example, reading areas are created with a variety of material by different authors according to certain specifics. So, modern techniques and technologies give all the ground for a teacher to work productively in both a classroom and via the Internet to help learners study effectively and efficiently.